Granulomatous Gastritis: A Clinicopathologic Analysis of 39 Biopsy Cases - Raja Jouini; Meriam Sabbah; Meriam Naija; Khanchel Fatma; Koubaa Wafa; Bibani Norsaf; Trad Dorra; Ouakaa Asma; Ben Brahim Ehsen (Journal of Spleen And Liver Research, 2018)
Introduction: Granulomas in gastric biopsy specimens are extremely rare. The final diagnosis of granulomatous gastritis is based on morphological findings, clinical and laboratory data. The aim of our study is to evaluate the clinical fields and to determine the etiology of gastric granulomatosis in our experience Patients and Methods: Thirty nine patients were reviewed retrospectively in the department of pathology of Habib Thameur between 2000 and 2018. Slides from all cases were stained by hematoxylin and eosin. The clinic-pathologic findings and the associated lesions were analyzed and the final etiology of the gastric granulomatosis was noted. Results: Biopsies from the 39 patients diagnosed as having granulomatous gastritis were reviewed. Mean age was 49 years (24 – 96) and sex ratio was 0,25 (M/F=8/31). Indication of endoscopy was gastric pain in 12 cases, chronic diarrhea in 6 cases, anemia in 2 cases, vomiting in 4 cases. Other symptoms were rare. Upper endoscopy was normal in 8 cases, showed antral gastropathy in 20 cases (erythematous in 6 cases, nodular in 8 cases and ulcerated in 6 cases). In four cases, fundic lesions were observed. Granuloma was unique in 14 cases and multiple in 25 cases. Localisation of granuloma was the antrum in 25 cases, the fundus in 7 cases, and both of them in 7 cases. An associated chronic gastritis was noted in 25 cases. Concerning the etiology, 10 of our patients had Crohn's disease while 6 of them had gastric tuberculosis. In five cases, H Pylori was the retained cause of gastric granulomatosis. In the other patients, the final diagnosis was sarcoidosis (n=3), foreign body reaction (n=1), yersiniosis (n=1). In our series, thirteen cases were unclassifiable. Conclusion: Although many cases remain unclassified, in most cases of granulomatous gastritis, a diagnosis of Crohn's disease or tuberculosis could be established. If this cases are excluded, an association between H. pylori and granulomatous gastritis cannot be ruled out. The others causes are extremely rare.
Keywords: hematoxylin